2022
DOI: 10.3389/fcosc.2021.752377
|View full text |Cite
|
Sign up to set email alerts
|

Why Geographical Indications Can Support Sustainable Development in European Agri-Food Landscapes

Abstract: Implementing the European Green Deal and transforming agricultural practices requires a wider and amplified policy toolbox. As many sustainability considerations are context-dependent, there is a need for instruments, which take individual characteristics of production landscapes into account. Food products with a particularly strong relationship to their landscape of origin can be marketed under the “Protected Designation of Origin” label (PDO). In this article, we analyze synergies between PDO production and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…GI standards seem more pertinent for those aspects which have an immediate connection to the affected region, i.e., socio-economic criteria or ecological criteria related to the preservation of specific landscape or biodiversity features. This is consistent with the empirical literature that suggests that GIs favour specific sustainability dimensions more than others [24,45]. It is also consistent with the general finding that stakeholder selfregulation along Ostrom's design principles seems most effective for localised sustainability challenges [46].…”
Section: Designing "Sustainable Gis"supporting
confidence: 90%
See 2 more Smart Citations
“…GI standards seem more pertinent for those aspects which have an immediate connection to the affected region, i.e., socio-economic criteria or ecological criteria related to the preservation of specific landscape or biodiversity features. This is consistent with the empirical literature that suggests that GIs favour specific sustainability dimensions more than others [24,45]. It is also consistent with the general finding that stakeholder selfregulation along Ostrom's design principles seems most effective for localised sustainability challenges [46].…”
Section: Designing "Sustainable Gis"supporting
confidence: 90%
“…Given its bottom-up and polycentric character, the GI system has itself been described as a sustainable policy instrument [22]. Indeed, empirical studies have highlighted the potential of GIs to contribute to different dimensions of sustainability [23][24][25][26]. However, some cases, including some of the most notorious GI "success stories" have shown that introducing GIs can also negatively affect various sustainability dimensions in the respective areas [19,27,28].…”
Section: Geographical Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the importance and complexity of sustainable development, apart from the competence of state authorities, provinces and local municipalities have numerous delegated competences regarding environmental matters. 9 In addition, mentioning sustainable development in the context of environmental protection directly sets the core of sustainability into the framework of protection of the environment and, in particular, natural values. Therefore, the Law on Environmental Protection explicitly prescribes the principle of sustainable development 10 and provides its meaning.…”
Section: Environmental Protection and Sustainable Developmentmentioning
confidence: 99%
“…PDO and PGI designations also play a vital role in sustaining rural economies by supporting local fruit producers [ 10 ]. In a bioeconomic context, this can foster rural development and create new bio-based value chains, thereby linking agricultural production with processing industries.…”
Section: Introductionmentioning
confidence: 99%